The Intricate Mechanisms of Functional Foods Oyster Mushroom and Fenugreek on Type 2 Diabetic Animal Model - Arafat Hassan Razon; Md. Alauddin; Nisat Farzana; Sanaullah Mazumdar; Md. Ruhul Amin; Md. Mahedi Hassan Tusher; Md. Asrafuzzaman; Nahid Hasan; Mahfuzur Rahman; Muhammad Saiedullah; Begum Rokeya; Md. Omar Faruque (Journal of Diabetes Research)
Mushrooms and fenugreek are widely used to reduce hyperglycemia, and fenugreek is also used as a culinary ingredient to enhance flavor and aroma. This study is aimed at investigating the underlying mechanisms of the hypoglycemic effects of mushrooms and fenugreek in a Type 2 diabetic rat model. Adenosine monophosphate (AMP)–activated protein kinase (AMPK) functions to reduce hyperglycemia through insulin-independent pathways and protects beta-cells. Diabetic model rats were administered standard diets supplemented with 5% oyster mushroom powder (mushroom-treated (MT) group) and 5% fenugreek seed powder (fenugreek-treated (FT) group) for 8 weeks. The results showed improvements in both glycemic and lipid profiles, with both oyster mushroom and fenugreek enhancing the phosphorylation of AMPK in muscle tissue. However, no effect on insulin secretion was observed. These findings suggest that both substances reduce hyperglycemia through an insulin-independent pathway. In silico analysis of both mushroom and fenugreek seed extracts revealed bioactive compounds having a strong binding affinity to α-glucosidase, which suggests mushroom and fenugreek supplements might control postprandial blood glucose levels.